Analysis of the Influence of the Quality of Infrastructure and Human Resources on the Effectiveness of the Building Licensing Process in Denpasar City, Bali Indonesia - Darma, I Putu Rizky Adhi; Putra, I Dewa Gede Agung Diasana; Dwijendra, Ngakan Ketut Acwin; Dewi, Anak Agung Diah Parami (Universitas Ibn Khaldun Bogor, 2025)
This study aims to analyze the influence of the quality of infrastructure facilities and human resources (HR) competence on the effectiveness of the building licensing process in Denpasar City. The change in regulations from Building Permits (IMB) to Building Approvals (PBG) under the Job Creation Law 2020 provides new challenges in implementing building permits, especially in areas with high levels of development, such as Denpasar City. This study uses a quantitative approach with the Partial Least Square-Structural Equation Modeling (PLS-SEM) method to test the contribution of infrastructure facilities and human resource competence to the effectiveness of licensing. The results show that the quality of infrastructure has a significant influence with an R-square value of 0.45 and a direct influence of 0.60, which means that improving the quality of infrastructure has a positive impact on the smooth licensing process. In addition, HR competence also has a significant influence on the effectiveness of licensing, with an R-square of 0.40 and a direct impact of 0.55. These two variables, when integrated, form an optimal service model that improves licensing efficiency and community satisfaction. These findings show that investment in infrastructure and human resource training focused on enhancing SIMBG's technical and operational skills is an important step to improve the quality of public services. This study provides recommendations to the local government of Denpasar City to increase investment in digital infrastructure, especially in the SIMBG licensing system, and carry out periodic training for employees involved in the licensing process. This recommendation is expected to support the implementation of PBG that is more effective, responsive, and to the needs of the community and permit applicants.